NF-κB inhibition rescues cardiac function by remodeling calcium genes in a Duchenne muscular dystrophy model - Jennifer M. Peterson (Nature Portfolio, 2018)
The molecular mechanisms leading to heart failure in patients with Duchenne muscular dystrophy are unclear. Here the authors show that NF-κB is activated in the heart of dystrophin-deficient mice and that its ablation rescues cardiac function through chromatin remodeling and activation of gene expression.